Use of 'tree tin' nesting sites by the Eurasian Treecreeper Certhia familiaris, with notes on nest composition. Issue 2 (3rd July 2019) - Goodall, Anne L.; Charles Deeming, D.; Biddle, Lucia E.
ABSTRACT: A corrugated bituminised roofing felt 'tree tin' originally provided to serve as a bat roost was adopted on a regular basis by Eurasian Treecreepers as nest sites. Data on nest construction under 'tree tins' are discussed.